Common pathogenetic mechanism involving human chromosome 18 in familial and sporadic ileal carcinoid tumors - Cunningham, Janet L.; Díaz de Ståhl, Teresita; Sjöblom, Tobias; Westin, Gunnar; Dumanski, Jan P.; Janson, Eva T. (Genes chromosomes & cancer, 2011)
Serotonin producing endocrine carcinoma of small intestine (ileal carcinoid) is a clinically distinct endocrine tumor. It is generally considered as a sporadic disease and its molecular etiology is poorly understood. We report comprehensive clinical and molecular studies of 55 sporadic and familial patients diagnosed with this condition. Nine pedigrees encompassing 23 affected subjects were established, consistent with autosomal dominant mode of inheritance. Familial and sporadic patients demonstrated indistinguishable clinical pictures. Molecular analyses of 61 tumors from 45 individuals, including eight familial and 37 sporadic patients, aimed at determination of global copy number aberrations using BAC and Illumina SNP arrays and gene expression profiling by Affymetrix chips. Chromosome 18 aberrations were identified in both sporadic and in familial tumors; 100% vs. 38%, respectively. Other, less frequent aberrations were also common for both groups. Global expression profiles revealed no differentially expressed genes. Frequent gain of chromosome 7 was exclusively observed in metastases, when patient matched primary tumors and metastases were compared. Notably, the latter aberration correlated with solid growth pattern morphology (P < 0.01), a histopathological feature that has previously been related to worse prognosis. The clinical and molecular similarities identified between sporadic and familial cases suggest a common pathogenetic mechanism involved in tumor initiation. The familial variant of ileal carcinoid represents a previously unrecognized autosomal dominant inherited tumor disease, which we propose to call Familial Ileal Endocrine Carcinoma (FIEC). Our findings indicate the location of a FIEC tumor suppressor gene near the telomere of 18q, involved in development of inherited and sporadic tumors. © 2010 Wiley‐Liss, Inc.